Mata Najwa Sebagai Cermin Demokrasi dan Representasi Kebenaran Dalam Media Alternatif - Pasah, Marip; Raharjo, Angga Sandhika; Almagfira, Anisa; Syahir, Fabhian Halky; Asmara, Daffi Allegra; Carina T., Joy Catherine; Carolina, Lavia Luky; Adfari, Tsabitah Rahmah; Abdullah, Nayla Putri; Yadila, Natasya; Amelia, Sabina Putri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes the president’s narrative through Habermas’ deliberative democracy framework and assesses the communication relations between the elite and the public within the IKN policy as a reflection of the quality of participatory democracy in Indonesia. The article aims to examine whether elite political communication can serve as an indicator of the overall quality of democracy itself. The research method employed is qualitative content analysis, examining Mata Najwa as a representation of democracy and an alternative media platform. Data were gathered from various media sources and academic references, and analyzed comprehensively to produce findings that are relevant, applicable, and contributive to the development of media and democracy discourse in Indonesia. Mata Najwa, hosted by Najwa Shihab, has become one of the most notable highlights within Indonesia’s media landscape. With a track record as an independent journalist, the program consistently discusses political, social, cultural, and societal issues through a critical, reflective, and credible approach. Each broadcast presents competent speakers and multiple perspectives, creating a comprehensive dialogic space. This approach not only provides information but also education, while enhancing public satisfaction and awareness. The Mata Najwa podcast plays a strategic role in fostering an open political discussion space in Indonesia. Through the episode “[Exclusive] Jokowi on IKN, Gibran, and ‘Put Jokowi on Trial’,” the program invited President Jokowi to respond to political issues, public criticisms, and national policies. This broadcast reflects values of national defense, ethical leadership, and political courage in facing contemporary challenges.